Atomic-layer-deposition-formed sacrificial template for the construction of an MIL-53 shell to increase selectivity of hydrogenation reactions. Issue 53 (14th June 2019) - Xu, Tiantian; Sun, Kai; Gao, Daowei; Li, Cuncheng; Hu, Xun; Chen, Guozhu
Abstract : Metal oxides deposited using ALD were chosen as sacrificial templates to design MOF-shell-based sandwich-type structures. Abstract : We developed a method for using atomic layer deposition (ALD)-formed layers of Al2 O3 as a sacrificial template to generate MIL-53(Al). The MOF shell in the CeO2 /Pd@MIL-53(Al) configuration not only stabilized the Pd nanoparticles, but also regulated the selectivity of the hydrogenation of unsaturated aldehydes. This work represents the first demonstration of ALD-formed layers of metal oxides serving as sacrificial templates in the design of MOF-shell-based sandwich-type structures.